2012
DOI: 10.5194/hess-16-3717-2012
|View full text |Cite
|
Sign up to set email alerts
|

Field data collection and analysis of canopy and litter interception in commercial forest plantations in the KwaZulu-Natal Midlands, South Africa

Abstract: Abstract. It is well accepted that the total evaporation in forested areas is greater than in grasslands, largely due to the differences in the amount of rainfall that is intercepted by the forest canopy and litter and due to higher transpiration rates. However, interception is the least studied of these components of the hydrological cycle. The study aims to measure and quantify the canopy and litter interception by Eucalyptus grandis, Pinus patula and Acacia mearnsii, at the Two Streams research catchment in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 20 publications
5
51
2
2
Order By: Relevance
“…The forest type in Helvey's study was similar to that of ours, and the estimated decrease in 3-year ET in our study (80.3 mm) is comparable with that reported by Helvey (1967), which suggests that forest floor evaporation could be accounted for by the decrease in litter interception after litter removal from the entire watershed. Bulcock and Jewitt (2012) reported 3-year litter interceptions of 160, 125, and 231 mm in Eucalyptus, Acacia, and Pinus stands, respectively. These values are also comparable with those of our study.…”
Section: Discussion Effect Of Litter Removal On Etmentioning
confidence: 99%
See 1 more Smart Citation
“…The forest type in Helvey's study was similar to that of ours, and the estimated decrease in 3-year ET in our study (80.3 mm) is comparable with that reported by Helvey (1967), which suggests that forest floor evaporation could be accounted for by the decrease in litter interception after litter removal from the entire watershed. Bulcock and Jewitt (2012) reported 3-year litter interceptions of 160, 125, and 231 mm in Eucalyptus, Acacia, and Pinus stands, respectively. These values are also comparable with those of our study.…”
Section: Discussion Effect Of Litter Removal On Etmentioning
confidence: 99%
“…Continuous field measurements of litter interception can only be obtained using a sheet-shaped weighing lysimeter (Schaap and Bouten 1997;Gerrits et al 2007Gerrits et al , 2010 or a permeable basin with a tipping bucket rain gauge to continuously monitor the water that drains from the litter layer into the soil (Bulcock and Jewitt 2012). However, these measuring devices are difficult to establish on sloping surfaces because the overlying litter can move downslope under the influence of gravity, which can alter the impact of raindrops on the forest floor.…”
Section: Introductionmentioning
confidence: 99%
“…The litter layer is an important component of forest ecosystems and its importance is often underestimated in water resource management (Schaap et al 1997, Levia et al 2005, Ilek et al 2015. More recent studies have added evidence of a substantial impact of litter on the water budget in semiarid shrubland and woodland with a substantial litter layer (Dunkerley 2000, Chang et al 2008, Bulcock & Jewitt 2012, Acharya et al 2017). However, the litter production dynamics, litter layer structure and hydrological properties of secondary forests in humid forest ecosystems, as well as their relevance in water conservation management have not been widely studied.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Bulcock and Jewitt (2012) also found that in precipitation events of 4 mm or less, 100 % interception commonly occurred in forest interception studies depending on antecedent conditions of the leaf litter and canopy. The variable weather conditions and the type of rainfall experienced have an effect on θ and therefore the water availability and DF water use.…”
Section: Discussionmentioning
confidence: 93%